Sequence stratigraphy and geometry of the carbonate platform in the Longwangmiao Formation (Toyonian), Cambrian, SW China - Wang, Guangwei; Gao, Huoqing; Zou, Huayao (Frontiers in Marine Science, 2025)
Carbonate platforms provide important sedimentary archives for paleoceanography and recording paleoenvironments. The aim of this study was to decipher the control of platform evolution and its constraint on the chemostratigraphic correlation in the Lower Cambrian at the eastern part of the Yangtze Platform. With the petrological observation, XRD, as well as C and O isotope analysis, two third-order sequences (SQ1 and SQ2) and six fourthorder sequences (PSQ1, PSQ2, PSQ3, PSQ4, PSQ5, and PSQ6) were recognized in the Longwangmiao Formation. Thirteen lithofacies (Lf-1–Lf-13) and three facies associations (shoreface, upper offshore, and lower offshore) were identified across the proximal to distal range of the platform. The correlation between logged outcrop sections suggested that the carbonate platform evolved from a homoclinal ramp in PSQ1 to a more distally deepened geometry in PSQ2, with this evolution driven by synsedimentary fault activity. From PSQ2 to PSQ3, the geometry evolved from a ramp to a rimmed platform associated with depleted d13C values and an increasing Chemical Index of Alteration (CIA) index. Such a transition of platform geometry may be attributed to the enhanced rate of carbonate production due to intense weathering and nutrient input. The final evolution of the Eastern Yangtze Platform (PSQ4) seemed to have been driven by falling relative sea levels and resulted in the formation of a flat-topped morphology, associated with subaerial exposure and depleted in d13C (LNE2). The two final sequences recognized in outcrops, PSQ5 and PSQ6, were only recognized in the distal reaches of the deposit and were interpreted to be “missed beats” in the sense that the sea level did not transgress the platform top. This study suggests the importance of carbonate production driven by chemical weathering on the control of platform geometry and sequence stratigraphy..